Efektivitas Metode Proyek dalam Mengembangkan Kreativitas Siswa Kelas 1 Sekolah Dasar - Selly Marselina; Muhamad Sofian Hadi (Universitas Muhammadiyah Bangka Belitung, 2025)
The focus of this research concerns the project method in developing children's creativity. It is very important for children's creativity to be developed from an early age so that children's intelligence and ability to express and produce something new can develop optimally. The purpose of this research is to determine the application of the project method to children and determine the effectiveness of the project method in developing the creativity of 1st grade elementary school students di SD 11 Sebagin. This research uses a qualitative descriptive method. Data collection techniques use observation, interviews and documentation. Then the content validity is validated through expert judgment. Next, the data analysis technique is carried out by reducing the data, presenting the data and then drawing conclusions (verification). From the research results it can be concluded that the project method is effective in developing the creativity of of 1st grade elementary school students di SD 11 Sebagin. By using the project method, children's creativity can develop optimally, as seen from children who like to ask questions, have a high curiosity, apart from that, children share ideas, interact with each other, cooperate with each other and learn. responsible for each group task.